2016
DOI: 10.21608/jppp.2016.52023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biofilterizers and Control Treatments on Roots Nodulation, Yield and Associated Weeds of Soybean Crop

Abstract: This study was carried out during 2013 and 2014 seasons to investigate the effect of different biofertilizers (microbin, phosphorine and rhizobecteren) and weeds control treatments (flauzifop-p-butyl, bentazon, flauzifop-p-butyl + bentazon, hand hoeing twice and three times) on roots nodulation, crop yield and associated weeds of soybean. The results showed that the biofertilizers and weeds control treatments significantly decreased the dry weight of grassy weeds, broad-leaved and total weeds. Also bio-fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Previous research also reported that the P. polymyxa fermentation broth increased plant growth (shoot length, root length, and biomass) in soybean, canola, kiwifruit, pepper, watermelon, rice, maize, potato, cucumber, beans, tomato, barley, Arabidopsis , and other ornamental plants [ 7 , 51 , 52 ]. It is also known that the 2,3-BDO secreted by bacteria stimulates root development, leading to increased uptake of nutrients and water and increased plant growth [ 4 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research also reported that the P. polymyxa fermentation broth increased plant growth (shoot length, root length, and biomass) in soybean, canola, kiwifruit, pepper, watermelon, rice, maize, potato, cucumber, beans, tomato, barley, Arabidopsis , and other ornamental plants [ 7 , 51 , 52 ]. It is also known that the 2,3-BDO secreted by bacteria stimulates root development, leading to increased uptake of nutrients and water and increased plant growth [ 4 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the increase in nitrous oxide caused by the use of chemical fertilizers affects global warming [ 3 ]. In order to solve these problems of chemical fertilizers, various researches on alternative plant growth promoting agents are in progress [ 4 7 ]. Among them, a promising alternative plant growth promoting agent is 2,3-butanediol (2,3-BDO).…”
Section: Introductionmentioning
confidence: 99%